Risedronate-loaded aerogel scaffolds for bone regeneration - Nahla El-Wakil; Rabab Kamel; Azza A. Mahmoud; Alain Dufresne; Ragab E. Abouzeid; Mahmoud T. Abo El-Fadl; Amr Maged (Taylor & Francis Group, 2023)
AbstractSugarcane bagasse-derived nanofibrillated cellulose (NFC), a type of cellulose with a fibrous structure, is potentially used in the pharmaceutical field. Regeneration of this cellulose using a green process offers a more accessible and less ordered cellulose II structure (amorphous cellulose; AmC). Furthermore, the preparation of cross-linked cellulose (NFC/AmC) provides a dual advantage by building a structural block that could exhibit distinct mechanical properties. 3D aerogel scaffolds loaded with risedronate were prepared in our study using NFC or cross-linked cellulose (NFC/AmC), then combined with different concentrations of chitosan. Results proved that the aerogel scaffolds composed of NFC and chitosan had significantly improved the mechanical properties and retarded drug release compared to all other fabricated aerogel scaffolds. The aerogel scaffolds containing the highest concentration of chitosan (SC-T3) attained the highest compressive strength and mean release time values (415 ± 41.80 kPa and 2.61 ± 0.23 h, respectively). Scanning electron microscope images proved the uniform highly porous microstructure of SC-T3 with interconnectedness. All the tested medicated as well as unmedicated aerogel scaffolds had the ability to regenerate bone as assessed using the MG-63 cell line, with the former attaining a higher effect than the latter. However, SC-T3 aerogel scaffolds possessed a lower regenerative effect than those composed of NFC only. This study highlights the promising approach of the use of biopolymers derived from agro-wastes for tissue engineering.